High-Intensity Focused Ultrasound for Prostate Cancer: Long-Term Followup and Complications Rate - Umberto Maestroni; Francesco Dinale; Roberto Minari; Paolo Salsi; Francesco Ziglioli (Advances in Urology)
Introduction. As it is well known, High Intensity Focused Ultrasound (HIFU) is a minimally invasive procedure for prostate cancer. Many investigators reported their series of patients, demonstrating the effectiveness of the treatment. The most majority of Authors, however, do not report the side effects and the complications of the procedure, which is the aim of our study. The diagnosis and management of complications is discussed, and the oncologic outcome is reported in terms of quality of life. Materials and Methods. We report our experience in 89 patients, low-, intermediate-, and high-risk patients according with D’Amico classification. All data collected along the study were analyzed, including side effects and complications of the procedure. Results. Our series demonstrates the effectiveness of the procedure, in line with larger series reported in literature by other investigators. The most important side effects are sexual function impairment and transient incontinence in a minority of cases. Minor complications are reported as well as rare cases of major complications, which can require surgical treatment.